Risk factors for Burkitt lymphoma in children in East Africa - Peprah, Sally; Ogwang, Martin D.; Kerchan, Patrick; Reynolds, Steven J.; Tenge, Constance N.; Were, Pamela A.; Kuremu, Robert T.; Wekesa, Walter N.; Sumb, Peter O.; Masalu, Nestory; Kawira, Esther; Magatti, Josiah; et al. (Research Square, 2019)
Endemic Burkitt lymphoma (eBL), a malignancy of immune B cells, is the most common childhood cancer in sub-Saharan Africa eBL is curable when it's identified early, but it's rapidly fatal without treatment Children in sub-Saharan Africa are over 50 times more likely to develop eBL than children living anywhere else in the world Unfortunately, few studies have examined the risk factors associated with eBL To address that gap, researchers conducted a study of eBL in children in three countries in East Africa They analyzed the relationship between eBL and infections, environmental, and genetic risk factors and focused their conclusions on results observed in at least two countries to minimize false-positives Risk of eBL was associated with low socio-economic status inpatient malaria treatment and living in areas targeted for malaria suppression In addition to exploring eBL risk factors, this study also demonstrates the potential to study cancer risk in East Africa and to detect, treat, or prevent eBL Learn more at emblem.cancer.gov Peprah et al. Risk factors for Burkitt lymphoma in East African children and minors. Int. J. Cancer. (2019)
Keywords: Cancer; Epidemiology; Burkitt lymphoma; Endemic burkitt lymphoma; Lymphoma; Sub-Saharan Africa; East Africa; Uganda